2018
DOI: 10.1142/s0219455418500761
|View full text |Cite
|
Sign up to set email alerts
|

Impact Response of Flying Objects Modeled by Positional Finite Element Method

Abstract: This paper analyzes the dynamic response of space and plane trusses with geometrical and material nonlinear behaviors using different time integration algorithms, considering an alternative Finite Element Method (FEM) formulation called positional FEM. Each algorithm is distinguished from each other by its specific form of position, velocity, acceleration and equilibrium equation concerning the stability, consistency, accuracy and efficiency of solution. Particularly, the impact problems against rigid walls ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…e use of such a formulation is justified by the capacity and simplicity of its application in the analysis of nonlinear problems as highlighted in Coda and Greco [17] and Greco and Coda [18]. For this reason, although relatively recent, the positional formulation has been the object of study of different researchers, as demonstrated in the works of Coda and Paccola [19], Maciel and Coda [20], Greco and Ferreira [21], de Oliveira and Greco [22], Sampaio et al [23], de Barros Cavalcante et al [24], Pascon and Coda [14], Carrazedo and Coda [25], Rabelo et al [15], and Ramos and Carrazedo [26].…”
Section: Introductionmentioning
confidence: 99%
“…e use of such a formulation is justified by the capacity and simplicity of its application in the analysis of nonlinear problems as highlighted in Coda and Greco [17] and Greco and Coda [18]. For this reason, although relatively recent, the positional formulation has been the object of study of different researchers, as demonstrated in the works of Coda and Paccola [19], Maciel and Coda [20], Greco and Ferreira [21], de Oliveira and Greco [22], Sampaio et al [23], de Barros Cavalcante et al [24], Pascon and Coda [14], Carrazedo and Coda [25], Rabelo et al [15], and Ramos and Carrazedo [26].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the authors' familiarity with the aforementioned positional formulation of the Finite Element Method, one of the motivations for using it in the present paper is due to its simplicity and applicability in analyses of nonlinear problems as highlight by the precursory authors of the formulation (Coda and Greco, 2004;Maciel and Coda, 2008). For this reason, although relatively recent, the positional formulation has been the object of study by several researchers, as demonstrated in the works of Coda and Paccola (2007), Greco and Ferreira (2009), Oliveira and Greco (2014), Sampaio et al (2015), Cavalcante et al (2017), Pascon and Coda (2017), Carrazedo and Coda (2017), Rabelo et al (2018), Fernandes et al (2018), and Ramos and Carrazedo (2020).…”
Section: Introductionmentioning
confidence: 99%